A CASE REPORT ON STEVENS-JOHNSON SYNDROME - Dharmarajan, Babu; Varghese, Sanil; T., Sachina B. (Journal of Health and Allied Sciences NU, 2014)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are a rare disease which is considered to be more devastating and fatal in nature. Usually symptoms may start with the involvement of epidermis and progress to the various manifestations. Early findings, symptomatic and supportive treatment will have the more positive impact on the outcome of the client.
Keywords: Toxic epidermal necrolysis; skin lesion; Erythematous macules